Immunoglobulin synthesis in the "resting" breast. Issue 6034 (28th August 1976) - Drife, J O; McClelland, D B; Pryde, A; Roberts, M M; Smith, I I
Abstract : Nulliparous women have a greater risk of developing breast cancer than women who have borne children, but so far no functional differences in breast tissue have been reported between parous women and nulliparae. Macroscopically and histologically normal breast tissue was obtained from 74 women of reproductive age during biopsy of benign breast lesions and was examined for the presence of plasma cells by immunfluorescence. Immunoglobulin synthesis was detected by an in-vitro culture technique. Synthesis of IgA was detected in 81% of specimans of IgG in 45%, and of IgM in 3%. IgA synthesis much more intense than IgG or IgM synthesis. Plasma cells containing IgA were seen in 71% of the specimens examined, and 88% of specimens had deposits of IgA in the ductules. The findings were not significantly incluenced by the nature of the condition necessitating biopsy or by oral contraception. Nulliparous women showed no cyclical changes, but among parous women IgA synthesis was more intense during luteal phase of the menstrual cycle. This suggests that after the first pregnancy the breast is more sensitive to progesterone.